Activity and Time Value of Public Passenger Transportation Users During the Covid-19 Pandemic in 2020 (Bus of Batik Solo Trans Corridor 4 in Surakarta) - Amirotul Musthofiah Hidayah Mahmudah; Syafi’I; Dewi Handayani; Slamet Jauhari Legowo; Widi Hartono (Indonesian Journal of Engineering Research, 2021)
The Covid-19 pandemic in 2020 has a significant impact on all countries' social and economic conditions, including Indonesia. It is fitting that social and economic changes also affect the transportation sector. The value of economic benefits in one public facility operation also depreciated due to the economic recession. One of the variables that can be reviewed is the time value of public passenger transportation users (AUP) to measure how much depreciation has occurred. This study specifically for travel is learning, using the bus mode Batik Solo Trans (BST) Corridor 4. Development of scenarios for questionnaires with stated preference methods, using the choice mode between motorbikes and AUP as an option, and the mode utility is approached with the equation multiple linear regression. The results of the analysis show that the time value of the user in the fleet is IDR 274.67 / hour for a distance of 8.35 km and the Time Value for a distance of 13.0 km = IDR 240.82 / hour with a Value of Activity (VoA) which is close to zero because the activity in the fleet has no financial value. This time value is considerably smaller than the AUP time value with the same intention of trip, studying, which was analyzed in 2015, which was IDR 4,708 / hour.